Shear-Wave Velocity Structure in Southeast Asia from the 2025 Mw 8.8 Kamchatka Earthquake Using Hilbert–Huang Transform - Kurniawan, Andri; Dani, Ilham; Erfani, Sandri (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
The 2025 Mw 8.8 Kamchatka earthquake generated long-period teleseismic surface waves recorded at stations in Australia (CTAO), Thailand (CHTO), and Indonesia (KAPI) at epicentral distances of 6,400–8,200 km. These records provide a useful dataset to probe crust and upper-mantle structure across contrasting Southeast Asian tectonic domains. We apply the Hilbert–Huang Transform (HHT) to vertical seismograms to extract dispersion from non-stationary wave trains. Seismograms are decomposed by empirical mode decomposition, and dispersion ridges in the Hilbert spectrum are tracked to identify frequency-dependent group arrivals. Group-velocity curves are smoothed with a low-order polynomial, and dual-frequency anchors are used to enforce phase-velocity continuity. Group velocities increase from 3.0 km/s at periods ≥150 s to 5.5 km/s at 40–60 s, while phase velocities span 3.3–4.6 km/s. Phase-velocity curves initialized with CRUST1.0 are inverted for 1-D shear-wave velocity (Vs), indicating crustal thicknesses of 30–40 km: thicker beneath CHTO, intermediate at CTAO, and thinner with a slower upper mantle beneath KAPI. These lithospheric variations are consistent with regional deformation inferred from GPS and InSAR. Overall, HHT yields stable dispersion measurements and reliable Vs models relative to global references, underscoring its utility in complex tectonic regions.